Relevance of Professional Journals for Canadian Educational Psychologists and Counsellor Educators - Bowd, Alan D. (Canadian Journal of Counselling and Psychotherapy, 2012)
One hundred and eighty members of educational psychology and allied departments in Canadian universities were surveyed regarding the journals they considered most relevant to their overall professional development. The results of the survey revealed that journal rankings related closely to professional interest areas. In addition, it was discovered that the Canadian Counsellor ranked first among the Canadian journals and ranked second among all journals cited.